Kebijakan untuk Meningkatkan Literasi AI di Kalangan Mahasiswa - Jelice Twista Sijabat; Putri Ayu Adelina Situmorang; Sophie Yuninda Saputri; M. Joharis (Pusat riset dan Inovasi Nasional, 2025)
This article discusses policies to improve AI literacy among college students. The development of technology in the digital era is increasingly rapid, and artificial intelligence (AI) has become an important part of various aspects of life, including education. College students as the next generation need to have good AI literacy in order to adapt to the changing times and face the challenges of the increasingly technology-based world of work. AI literacy is not only about understanding how this technology works, but also how to use it effectively and ethically in academic and professional life. The research method used in this study is a descriptive qualitative method, with data collection techniques, namely interviews and documentation studies that aim to examine the development of technology in the increasingly rapid digital era, and artificial intelligence (AI) has become an important part of various aspects of life, including education. The results of the study are then narrated in descriptive form. It can be concluded that AI literacy has an important role in improving the effectiveness of student learning and preparing them for competition in an increasingly technology-based world of work.